Effect of Sodium Silicate on the Strength and Permeability Properties of Ultrafine Cement Grouted Sands - Avcı, Eyübhan; Deveci, Emre; Gokce A. (American Society of Civil Engineers (ASCE), 2021)
In this experimental study, the effect of sodium silicate (SS) added into an ultrafine-cement-suspension injection on the strength and permeability properties of grouted sand samples was investigated. The experiment started with a test for identifying the bleeding and viscosity values and setting times. This was followed by injecting sand samples prepared in different gradations with ultrafine cement (UC) with and without SS additive. In the experiments, 1.0, 1.5, 2.0, and 2.5 were used as the water:cement ratios, and 1%, 3%, and 5% were used as the SS additive ratios. Unconfined compression tests were performed on the sand specimens that were successful in the injection tests on days 3, 7, 14, 28, 56, and 90; and permeability tests were performed on days 7, 28, 56, and 90. While viscosity values increased with the addition of SS into the UC, bleeding values and setting times decreased. Injectability slightly decreased with the addition of SS into the UC. The addition of SS into the UC-suspension injection increased the unconfined compressive strength. Injected samples gained strength faster with the addition of SS into the UC. Adding sodium silicate into the UC-suspension injection reduced permeability values. In the experimental study, it was observed that the addition of SS additive into the UC improved the permeability and strength properties of sand samples after injection.
Keywords: Injectability; Permeability; Sodium silicate; Ultrafine cement; Unconfined compressive strength